2020
DOI: 10.1097/ijg.0000000000001609
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Travel Distance to Postoperative Follow-up Care on Glaucoma Surgery Outcomes

Abstract: Précis: This study addresses the paucity of literature examining glaucoma patients’ distance from clinic on postoperative follow-up outcomes. Greater distance from clinic was associated with higher likelihood of loss to follow-up and missed appointments. Purpose: To investigate the relationship of patient travel distance and interstate access to glaucoma surgery postoperative follow-up visit attendance. Methods and Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…143 Recent studies of minimally invasive glaucoma surgeries in non-Hispanic and Hispanic Black patients have shown good outcomes with certain minimally invasive glaucoma surgeries procedures. 144e146 Aside from race and ethnicity, potential disparities in rates of procedural glaucoma treatment and follow-up have been identified by age, 147 region, 148 provider type, 148 and distance from provider, 149 among other factors.…”
Section: Epidemiology Of Disparities By Eye Diseasementioning
confidence: 99%
“…143 Recent studies of minimally invasive glaucoma surgeries in non-Hispanic and Hispanic Black patients have shown good outcomes with certain minimally invasive glaucoma surgeries procedures. 144e146 Aside from race and ethnicity, potential disparities in rates of procedural glaucoma treatment and follow-up have been identified by age, 147 region, 148 provider type, 148 and distance from provider, 149 among other factors.…”
Section: Epidemiology Of Disparities By Eye Diseasementioning
confidence: 99%
“…In the particular case of the Kittner Eye Center and for this study population, the university's financial assistance program available to uninsured patients may also have made cost less of a barrier to care and thus increased follow-up rates. The previously discussed study by Funk et al 8 of a postsurgical glaucoma patient population which was served by the same clinic suggested insurance and socioeconomic status did affect loss to follow-up. They found that patients with Medicaid insurance were statistically more likely to be lost to follow-up after glaucoma surgery than patients with Medicare plans and also on average lived >12 miles from the clinic further than Medicare patients.…”
Section: Discussionmentioning
confidence: 91%
“…In this group of postsurgical patients with glaucoma, 20.1% of the study population and 37% of patients living .50 miles from the clinic were lost to follow-up during the 3-month postoperative period. 8 Other studies have shown distance from the clinic to be a challenge for patients with diabetes and other chronic retinal conditions seeking routine ophthalmologic care. [4][5][6][7] Sloan et al 4 found that patients with diabetes living .20 miles from the nearest ophthalmologist were 33% less likely to receive eye examinations during their study follow-up period than patients living closer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of distance on LTFU may be due to long travel time in addition to appointment time and increased expenses from fuel, food, or lodging. Distance has been noted as an important factor contributing to LTFU in other contexts including bariatric surgery, glaucoma surgery, and HIV 21,22,36,37 . Clinicians should be aware of the challenges in attending appointments for patients who live far away, prioritize open and honest communication, and offer potential resources that may help.…”
Section: Discussionmentioning
confidence: 99%